2003
DOI: 10.2169/internalmedicine.42.704
|View full text |Cite
|
Sign up to set email alerts
|

Subacute Thyroiditis with Highly Positive Thyrotropin Receptor Antibodies and High Thyroidal Radioactive Iodine Uptake

Abstract: (Internal Medicine 42: [704][705][706][707][708][709] 2003)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…There have been individual reports of a moderately high RAIU in SAT. Sumie et al report a patient with SAT and RAIU of 17% that they thought was transitory due to high Trab levels [5]. In their paper, they also mention that few other authors have reported high RAIU in SAT patients.…”
Section: Discussionmentioning
confidence: 91%
“…There have been individual reports of a moderately high RAIU in SAT. Sumie et al report a patient with SAT and RAIU of 17% that they thought was transitory due to high Trab levels [5]. In their paper, they also mention that few other authors have reported high RAIU in SAT patients.…”
Section: Discussionmentioning
confidence: 91%
“…We also found a cut-off (2 IU/L) that is slightly higher than the manufacturer-provided cut-off, though with high sensitivity (97.55) and specificity (100%) for diagnosing Graves’ disease. Several studies have demonstrated suboptimal diagnostic accuracy [ 19 - 21 ]. As 100% sensitivity was obtained at 1.4 IU/L, we suggest 99m-Tc thyroid scintigraphy for thyrotoxicosis patients with TSHrAb between 1.4 and 2.0 IU/L is prudent.…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 18 ] Similarly, subjects with subacute thyroiditis are also known to have positive TRAb in studies. [ 20 21 22 ] In some of these cases, the presence of increased radioactive iodine uptake suggests the presence of concomitant GD. [ 22 ] TRAb was found to be positive in people with painless thyroiditis.…”
Section: Discussionmentioning
confidence: 99%